Effect of perioperative transdermal nicotine patch on postoperative pain: A systematic review and meta-analysis - Bharat Yalla; Puneet Khanna; Soumya Sarkar; Deepika Lal; Ankita Maheshwari; Manish Gupta; Bhavuk Garg (Indian Journal of Anaesthesia)
Background and Aims: Nicotine replacement therapy (NRT) has emerged as a potential intervention for managing perioperative pain. However, their effectiveness remains unclear, as previous studies neither considered the effect of the route of administration nor differentiated the effect between smokers and non-smokers. This systematic review and meta-analysis aimed to determine the effect of a perioperative transdermal nicotine patch on postoperative pain in both smokers and non-smokers compared with a placebo. Methods: We performed a meta-analysis of randomised controlled trials (RCTs) comparing the effects of transdermal nicotine and placebo on postoperative pain. Databases of MEDLINE, EMBASE, CENTRAL, CINAHL, Google Scholar, Web of Science, and the Cochrane Central Register of Controlled Trials were searched. This systematic review and meta-analysis followed the PRISMA guidelines. The findings were evaluated using forest plots and expressed as relative risk (RR) or mean difference (MD) for primary and secondary outcomes. Results: Twelve studies included in the analysis showed no significant difference in pain scores (NRS) at 24 h between the two groups, with an MD −0.24 [95% confidence interval (CI): −0.55, 0.07; P = 0.13] (I2 = 77%, P < 0.00001), and there was no significant difference in postoperative opioid consumption (morphine equivalent) MD −0.92 (95% CI: −5.04, 3.21; P = 0.66) (I2 = 23%, P = 0.27). Similarly, the two groups had no significant differences in the time to first rescue analgesia, postoperative nausea and vomiting (PONV), or patient satisfaction. However, the required information size was not achieved for the outcomes of postoperative opioid requirement, reduction in postoperative pain, PONV, and the time for rescue analgesia. Conclusion: The perioperative transdermal nicotine patch did not significantly reduce postoperative pain scores compared with placebo. There appears to be a significant reduction in smokers, but the evidence is inadequate to conclude this finding.